UTILIZATION OF DIGITAL TECHNOLOGY IN DEVELOPING MARKETING STRATEGIES FOR MSME PRODUCTS - Faisal Hasbullah Batubara (Jurnal Ilmiah MEA (Manajemen, Ekonomi, & Akuntansi), 2022)
In current era, digital technology is very familiar to people of all ages. Utilizing digital technology effectively can have a positive effect on its users. One is applying digital technologies to generate promotion for MSME actors' business products. This study intends to assess the role of digital technology in the development of marketing management for small and medium-sized enterprise (SME) products. This study employs a qualitative, descriptive methodology. The results of the study indicate that the digital marketing strategy of micro, small, and medium-sized enterprises (MSMEs) does not immediately replace conventional marketing, but rather strikes a balance between online and offline activity. The exchange between digital and conventional marketing methods signifies a transition in marketing strategy, from segmentation and targeting to customer community confirmation, brand positioning & differentiation to personality clarification and brand codification. This research also reveals various digital marketing tactics, including 1) the use of Influencers or KOL; 2) the use of Social Media Ads; 3) Google My Business; 4) Search Engine Marketing (SEM); 5) Email Marketing; and 6) the use of the TikTok app.